Contemporary bioethics : Islamic perspective - Al-Bar, Mohammed Ali (Springer International Publishing, 2015)
This book discusses the common principles of morality and ethics derived from divinely endowed intuitive reason through the creation of al-fitr' a (nature) and human intellect (al-'aql). Biomedical topics are presented and ethical issues related to topics such as genetic testing, assisted reproduction and organ transplantation are discussed. Whereas these natural sources are God's special gifts to human beings, God's revelation as given to the prophets is the supernatural source of divine guidance through which human communities have been guided at all times through history. The second part of the book concentrates on the objectives of Islamic religious practice - the maqa' sid - which include: Preservation of Faith, Preservation of Life, Preservation of Mind (intellect and reason), Preservation of Progeny (al-nasl) and Preservation of Property. Lastly, the third part of the book discusses selected topical issues, including abortion, assisted reproduction devices, genetics, organ transplantation, brain death and end-of-life aspects. For each topic, the current medical evidence is followed by a detailed discussion of the ethical issues involved.